Creating a new legal form: the GmbH - Guinnane, Timothy (Economic Growth Center, Yale University, 2020)
The most common business enterprise form in Germany today is the Gesellschaft mit beschränkter Haftung (GmbH). The GmbH offers entrepreneurs the partnership's flexibility combined with limited liability, capital lock-in, and other traits associated with corporations. Earlier enterprise forms such as the partnership and corporation were codified versions of longstanding practice; the GmbH, on the other hand, was the lawgiver's creation. Authorized in 1892, the GmbH appeared during a period of ferment in German enterprise law and was an early example of the
10419/227652
Keywords: Graue Literatur; Rechtsform; GmbH; Rechtsgeschichte; Deutschland (bis 1945); 1892